PERANAN MIKORIZA VESIKULAR ARBUSKULAR (MVA) UNTUK MENINGKATKAN RESISTENSI TANAMAN TERHADAP CEKAMAN KEKERINGAN DAN KETERSEDIAAN P PADA LAHAN KERING - . Masria (Partner, 2008)
Exploiting of Mycorrhiza Vesicular Arbuscular (MVA) to Increase Crop Resistance to Dryness Grasp and Availability of P at Dry farming. Dryness grasp and nutrient deficient especially element of nutrient P is two main limiting factors at dry farming. Both the things will influence growth and crop productivity. One of alternative which applicable to overcome dryness grasp problem and deficient P is by exploiting Mycorrhiza mushroom. Mycorrhiza is form of association of mushroom with high level crop root. One of type Mycorrhiza which now gets serious attention is Mycorrhiza Vesicular Arbuscular (MVA). Association characteristic of Crop with this MVA enables crop can permeate water and nutrient in condition of dryness grasp and element deficient of nutrient especially P. This thing is enabled by MVA to have network hypa external which is wide and diameter which smaller than root fur and enzyme fosfotase capable to dissolve nutrient P to become available and permeates water, at the time of crop root had unable to again permeates it.Keywords: Mycorrhiza Vesicular Arbuscular, Dryness Grasp and Availability of P.